PENCEGAHAN TINDAK PIDANA PENCABULAN ANAK DI BAWAH UMUR MENURUT PERATURAN PERUNDANG–UNDANGAN DAN HUKUM ISLAM - Afrahul Fadhilah Sitorus, Anwar Sadat Harahap (NERACA KEADILAN, 2023)
This research is about Prevention of Criminal Acts of Obscenity of Underage Children According to Legislation and Islamic Law in the City of Lubuk Pakam to find out how to prevent criminal acts of molestation of minors according to legislation and Islamic law Data collection activities in this study are by collecting data secondary in the form of laws and regulations, articles or other documents needed to be categorized according to the appropriate grouping. In this study the authors used library research techniques and field research to collect and compile the necessary data. After conducting research and discussing the prevention of criminal acts of sexual abuse of minors according to laws and regulations and Islamic law in the city of Lubuk Pakam, Islam has provided rules in social relations such as politeness in dress ethics, ethics in looking at someone in human relations. therefore the occurrence of acts of sexual harassment is an immoral act. Islam commands us to guard our views towards anyone except with their husbands, their children, their siblings, their parents, their children.